Implementation Local Government Law No. 15 Of 2011 On The Implementation Of Hygiene In Village Way Acai Riverbank Mhorock Abepura District Jayapura - Korwa, Ferry Yan (Advances in Social Sciences Research Journal, 2017)
Communications Policy Implementation Performance Against Regional Regulation No. 15 Year 2011 on the Implementation of Hygiene it can be concluded as follows: 1) .Variable of data on Communication Policy indicates that communications made in the implementation of Operation Cleanliness in river Acai Mhorock Wai village Abepura District Jayapura City is already effective, the information distribution process (Transmission of Information), Information Clarity and Consistency of Information Effectively work already. This fact is supported by the results of Recapitulation of data on communication policy with effective variable categories Obtain a frequency response of 10 (43%) of the 23 respondents who Gave responses. This means that communications made in the implementation the organization of cleanliness has been running. 2) Implementation Performance rule. Rule with Number 15 Year 2011 concerning Cleanliness in river Acai Wai Village Mhorock Abapura Jayapura city district on the Recapitulation say that variable implementation performance said to be high, this situation Proves of the Recapitulation of data on the variable performance with the acquisition Implementation frequency of 12 (52%) with a high response categories indicates that access, coverage and service delivery has been high in the implementation of the program for implementation of hygiene in river Acai Mhorock Wai village Abepura District Jayapura City. 3) .Relate between variables Communication Policy with variable Implementation performance PERDA Number 15 Year 2011 on the Implementation of Hygiene, starting from the results of research conducted it has been known that there is a significant correlation between the variables for Communication Policy (X) with variable performance PERDA No. 15 Implementation in 2011 on the organization of cleanliness in river Acai Mhorock Wai village Abepura District Jayapura City.